Pre-Prosthetic Orthodontic Treatment Using Personalized Elastic Separators for Optimization of Emergence Profile in Esthetic Crowns: A Clinical Report - Freitas Júnior, Amilcar C. [UNESP]; Silva, Antonio M. (Wiley-Blackwell, 2012)
Restoring a misaligned tooth with an inadequate contact point is a challenge to the practitioner. In some instances, teeth that could be repositioned and adequately restored are extracted. Thus, the aim of this article was to describe a treatment using orthodontic and prosthetic techniques to restore esthetics and function in a patient with a distally drifted maxillary lateral incisor. The patient's functional and esthetic expectations were successfully met with the outlined treatment.
Keywords: Tooth movement; tooth drifting; prosthodontics; pre-prosthetic orthodontics; adjunctive orthodontics; multidisciplinary care